A hygrothermal modelling approach to water vapour sorption isotherm design for mesoporous humidity buffers - Sarce, Fernando; Hall, Matthew R.; Sangchoom, Wantana; Mokaya, Robert (Elsevier, 2015)
This paper describes the development of a design technique using hygrothermal numerical modelling for top-down predictive design and optimisation of water vapour sorption isotherms to match any humidity buffering application. This was used to inform the design and synthesis of two new mesoporous silica (MS) materials suitable for specific applications. To validate the technique, the new materials were experimentally assessed using gravimetric dynamic vapour sorption (DVS). The experimental isotherms closely matched the optimised isotherm predictions from the design stage, and a positive correlation was observed between the rate of change in adsorbed water content, Δw and the time taken to exceed the permissible upper limit of humidity, φi,U in a closed environment. A positive non-linear correlation was determined between the interior volumetric moisture load, ωml and the mass of adsorbent required to fully achieve humidity buffering between specified lower/ upper limits (φi,L and φi,U). The kinetics of water vapour sorption/ desorption were found to have general agreement when using the current hygrothermal numerical model. Current hygrothermal models appear to significantly underestimate the rate of adsorption/ desorption in rapid-response mesoporous silica type materials. This is perhaps largely due to the current lack of consideration for scanning curve prediction within hysteresis loops and so is a priority for future research.